2007
DOI: 10.1248/bpb.30.1745
|View full text |Cite
|
Sign up to set email alerts
|

Cryptomeria japonica-Induced Allergic Conjunctivitis in Mice

Abstract: Japanese cedar pollen (Cryptomeria japonica, Cry j) is the most common allergen causing pollinosis in Japan. However, short ragweed pollen is used commonly as the antigen for experimentally-induced allergic conjunctivitis (EC) and Cry j-induced EC in mice has not been published. We actively immunized BALB/c mice with Cry j, and then performed a challenge with eye drops containing Cry j. We evaluated the early phase and late phase reactions in the conjunctiva, using Evans blue dye leakage and eosinophil infiltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It was reported that anti-histamine is a potent inhibitor of the early-phase reaction. 12,14 Ketotifen instillation showed the most potent inhibitory effect on plasma exudation after single RW challenge. mice.…”
Section: Effect Of Cyclosporine a Eye Drops On The Itch-scratch Respomentioning
confidence: 93%
“…It was reported that anti-histamine is a potent inhibitor of the early-phase reaction. 12,14 Ketotifen instillation showed the most potent inhibitory effect on plasma exudation after single RW challenge. mice.…”
Section: Effect Of Cyclosporine a Eye Drops On The Itch-scratch Respomentioning
confidence: 93%
“…The mice also had access to normal chow and drinking water ad libitum. Experimental allergic conjunctivitis due to Japanese cedar pollen was induced by a modified version of a previously described protocol 7. In brief, 0.2 mg of Japanese cedar pollen (Hayashibara, Okayama, Japan) was mixed with alum (2.5 mg) and injected intraperitoneally twice with an interval of 7 days between injections.…”
Section: Methodsmentioning
confidence: 99%
“…Then, an RW challenge was introduced into the left eye with eye-drops, while the right eye was challenged with PBS. Thirty minutes later, the conjunctivas were harvested and weighted, and EB was extracted from the conjunctivas and then measured according to previously described method 12. Data are presented as the differences in the EB levels (μg)/tissue weight (g) between the left and right eyes.…”
Section: Methodsmentioning
confidence: 99%